Tears of salt : - Bartolo, Pietro (W.W. Norton & Company, 2018)
Situated more than one hundred miles off Italy’s southern coast, the rocky island of Lampedusa has hit world headlines in recent years as the first port of call for hundreds of thousands of African and Middle Eastern refugees fleeing civil war and terrorism and hoping to make a new life in Europe. Dr. Pietro Bartolo, who runs the lone medical clinic on the island, has been caring for many of them―both the living and the dead―for a quarter century. Tears of Salt is Dr. Bartolo’s moving account of his life and work set against one of the signal crises of our time. With quiet dignity and an unshakable moral center, he tells unforgettable tales of pain and hope, stories of those who didn’t make it and those who did.